2015
DOI: 10.1021/acsami.5b10734
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale, Highly Efficient, and Green Liquid-Exfoliation of Black Phosphorus in Ionic Liquids

Abstract: We developed a facile, large-scale, and environmentally friendly liquid-exfoliation method to produce stable and high-concentration dispersions of mono- to few-layer black phosphorus (BP) nanosheets from bulk BP using nine ionic liquids. The prepared suspensions can stabilize without any obvious sedimentation and aggregation in ambient air for one month. In particular, the concentration (up to 0.95 mg mL(-1)) of BP nanoflakes obtained in 1-hydroxyethyl-3-methylimidazolium trifluoromethansulfonate ([HOEMIM][TfO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 30 publications
10
145
0
5
Order By: Relevance
“…This is not surprising since i) the sample was prepared on an oxidized Si substrate and ii) the fact that phosphorene flakes have been shown to readily react in air to form an oxide . The lattice spacing of our phosphorene sheet was measured to be 0.25 nm, which is in agreement with previous literature (Figure i) …”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 90%
See 2 more Smart Citations
“…This is not surprising since i) the sample was prepared on an oxidized Si substrate and ii) the fact that phosphorene flakes have been shown to readily react in air to form an oxide . The lattice spacing of our phosphorene sheet was measured to be 0.25 nm, which is in agreement with previous literature (Figure i) …”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 90%
“…The transmission electron microscopy (TEM) image illustrated in Figure e reveals that our phosphorene is an ultrathin nanosheet. Selected area electron diffraction (SAED) was further used to confirm the high‐quality single‐crystal structure of our phosphorene (see Figure e inset), which is consistent with previous reports . The elemental mapping in Figure f–h indicates that our sample consists of mainly phosphorus with a slight amount of oxygen.…”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 87%
See 1 more Smart Citation
“…ILs are presented by researchers for efficient exfoliation of 2D materials to obtain a stable yield with a high concentration of the suspended nanoflakes 200, 201, 202, 203. ILs exhibit viscosities that are 1−3 orders of magnitude more than those of conventional organic solvents; this influences the rate of mass transport within the solution by preventing the BP nanosheets from restacking 198, 200.…”
Section: Fabrication Of Few‐layered Bpmentioning
confidence: 99%
“…For the latter, several organic solvents such as N ‐methyl pyrrolidone (NMP), N , N ‐dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and cumyl hydroperoxide (CHP) have been utilized to prepare BP nanosheets on a large scale. To be environmentally friendly, ionic liquids have been used in lieu of these solvents, and large concentrations of BP nanosheets (≈0.95 mg mL −1 ) with stability under ambient conditions have been produced . Guo et al reported that the addition of a proper amount of alkali (NaOH) to NMP could boost the yield and improve the stability of BP nanosheets .…”
Section: From Bulk To 2dmentioning
confidence: 99%